A Case of Pulmonary Artery Sling Anomaly with Tracheal Stenosis and Management of Difficult Airway - Torun, Emine Gulsah; Yazici, Mutlu U.; Azapagası, Ebru; Örün, Utku A.; Cinar, Hasibe G.; Koc, Murat (Journal of Pediatric Intensive Care, 2020)
Pulmonary artery sling is a rare congenital vascular abnormality, where the left pulmonary artery originates from the right pulmonary artery, passes between trachea, and esophagus and reaching the left hilum. Cough, wheezing, and difficulty in feeding are three major symptoms. Untreated pulmonary sling carries high morbidity and mortality, most of which is due to the airway and other associated anomalies. Herein, we reported a 40-day-old male infant who admitted to the pediatric intensive care unit with progressive respiratory distress and diagnosed with left pulmonary sling with tracheal stenosis. We discussed the diagnosis and management of pulmonary artery sling and present the successful use of laryngeal mask in difficult airway management.
Keywords: computed tomography angiography; infant; in vitro fertilization; laryngeal mask airway; pulmonary artery sling